SEM and EDS Analysis Used in Evaluation of Chemical Pre-treatment Based on Nanotechnology - Svobodova, Jaroslava (Manufacturing Technology Journal, 2014)
The most important aim of chemical pre-treatment is the removal of contaminants, corrosion products etc. from the material surface and obtaining such a basic material surface, which will provide sufficient corrosion resistance of the base material and suitable conditions for the adhesion of paints or other finish coatings to steel material. When selecting the method of chemical pre-treatment of the base material surface it should be considered whether the degree of preparation provides the required level of cleanliness of the surface and also the surface roughness and surface profile for the coating to be applied to the base material after chemical pre-treatment. The paper focuses on SEM and EDS analysis used in evaluation of chemical pre-treatment based on nanotechnology. These chemical pre-treatments are excluded on low carbon steel sheet. On the surface of low carbon steel sheet were excluded coatings of chemical pre-treatments (Fe phosphate, coating based on nanotechnology) and has been studied character of excluded layers on electron microscope.
Keywords: SEM; EDS analysis; chemical pre-treatment; phosphating; nanopassivation